Investigation and analysis of interleaved dc-dc boost converter for grid-connected photovoltaic energy system - Mehmet Buyuk (MANAS: Journal of Engineering)
In this study, we focused on the synthesis of polymeric hydrogels that will support the sorption and controlled release of urea, which is a rich nitrogen source, from aqueous solutions and their usability in agricultural applications. N, N-Dimethylacrylamide (DMAAm) and Starch (St) were selected as monomers, and their superior properties, such as chemical stability, high sorption properties, biocompatibility, and the presence of modifiable groups, were utilized. A redox polymerization technique was used to create a poly(DMAAm-co-St)-based hydrogel that was then modified with acidic and basic agents to improve the properties of starch. The synthesized acid- and base-modified hydrogels were named DSt, DSt1, and DSt2, respectively. Swelling analyses were performed to examine the structural and morphological properties of DSt, DSt1, and DSt2 hydrogels, and Fourier-Transform Infrared Spectroscopy (FT-IR) and Thermogravimetric Analyzers (TGA) were used. Intense cross-linking, porosity, and the presence of hydrophilic groups were successfully detected by instrumental analysis and swelling results. The successful results of urea sorption by DSt, DSt1, and DSt2 hydrogels show that they can both minimize the harmful effects of urea in the environment and contain the nitrogen necessary for plants. At the same time, urea sorption behaviors were evaluated in terms of sorption isotherms and thermodynamic properties, and it was observed that urea sorption conformed to the Langmuir isotherm. The urea release results showed that DSt, DSt1, and DSt2 hydrogels exhibited different release properties in different pH solutions, and these results reached 94% at pH 6–8, 100% at pH 6, and 100% at pH 8–10, respectively. As a result of the gradual decrease in the water resources on the earth, the increase in the use of fertilizers in agricultural production, and the insufficient use of fertilizers, our study draws attention to the development and support of materials that absorb/store water, and forms of controlled release fertilizers and provides potential ease of application